The Equilibrium Rate of Unemployment and the Real Exchange Rate: An Unobserved Components System Approach - Hans Lindblad; Peter Sellin (Sveriges Riksbank, 2003)
We set up and estimate a structural unobserved components open economy model for the rate of unemployment and the real exchange rate in Sweden. This approach enables us to simultaneously determine changes in both cyclical and equilibrium rates. Our results show that the Natural Rate/NAIRU has increased by approximately 1.5 percentage points since the 1970s, driven by a depreciation of the equilibrium exchange rate, changes in taxes, active labor market policies and demographic factors. Thus, the results indicate that the dramatic changes in the Swedish unemployment rate during the 1990s mainly was a cyclical phenomenon. After five devaluations in the 1970s and early 1980s the krona was allowed to float on 19 November 1992. The depreciating trend continued during the floating rate period. Our model successfully explains this development as being driven by changes in terms of trade, demographics and structural government deficits. The change in the rate of inflation is found to be quite sensitive to the unemployment gap. An increase in cyclical unemployment by 1 percentage point will reduce inflation by approximately 0.6 percentage points within a year.
Keywords: C32; E24; E31; E32; F31; F41; 330; Natural Rate; NAIRU; Equilibrium real exchange rate; Phillips curve; Unobserved-components model